2008
DOI: 10.1111/j.1365-2702.2008.02374.x
|View full text |Cite
|
Sign up to set email alerts
|

Day surgery: patients’ felt abandoned during the preoperative wait

Abstract: Crucially health professionals need to facilitate person-centred and continuity of care throughout the day surgery experience. Using dynamic interpersonal skills, such as active listening 'holding''containment' and attunement to reduce anxiety and feelings of abandonment in the preoperative period. Moreover, being alert to verbal utterances, para-language and non-verbal cues demonstrated by the patient. Specific information about delays regarding the timing of procedures needs to be carefully explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 34 publications
2
100
0
4
Order By: Relevance
“…One patient felt the wait could increase pre-operative anxiety; these comments are similar to those in the study by Gilmartin and Wright (2008) where patients felt the pre operative wait was long. The letter that is sent to patients prior to attending for their procedure could be adapted to state that there may be a waiting period and as such patients should bring material to occupy them such as a book or music.…”
Section: Discussionsupporting
confidence: 69%
“…One patient felt the wait could increase pre-operative anxiety; these comments are similar to those in the study by Gilmartin and Wright (2008) where patients felt the pre operative wait was long. The letter that is sent to patients prior to attending for their procedure could be adapted to state that there may be a waiting period and as such patients should bring material to occupy them such as a book or music.…”
Section: Discussionsupporting
confidence: 69%
“…In day surgery, patients also need counselling on the use of analgesics and pain assessment (Rhodes et al, 2006, Stomberg et al, 2008 counselling as well as on rehabilitation, such as knee extension and flexion, and in how to use mobility aids (such as crutches) and for how long (Pieper et al, 2006, Gilmartin, 2007 Patients also want to know about the possible complications (Gilmartin & Wright, 2008), nutrition (Rhodes et al, 2006, Fredericks et al, 2010 and what health changes are normal or not after surgery (Fagermoen & Hamilton, 2006). Having an opportunity to meet with healthcare staff after day surgery is important to patients (Rhodes et al, 2006, Gilmartin, 2007, Stomberg et al, 2008, Knier et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…One approach NHS trusts can use to achieve this is to transfer most of their elective care to day surgery (Lau and Brooks 2001, Jackson 2007, Graham et al 2012 The NHS Modernisation Agency (2004) identified ten high-impact changes for service organisations to improve service provision. The top change on this list is to 'Treat day surgery (rather than inpatient surgery) as the norm for elective surgery', thereby increasing day surgery rates and reducing the length of post-operative stays (Jackson 2007, Gilmartin andWright 2008). This not only addresses financial constraints, but assists in bed management in acute services (Graham et al 2012).…”
Section: Archiveaspxhtml]mentioning
confidence: 99%
“…The literature suggests that NHS Trusts have had to increase the number of day surgery procedures performed in response to a reduction in the number of acute inpatient beds (Coley et al 2002, Gilmartin and Wright 2008, Rastogi and Vickers 2009, Ng and Vickers 2013. In practice, there appears to be a national shortage of acute inpatient beds.…”
mentioning
confidence: 99%